Automatización del secador de bandejas del laboratorio de operaciones unitarias – Facultad de Ingeniería para controlar el proceso de secado - Loza Zambrano, Diego Andrés (2019)
Industrial automation is a fundamental tool for the control and improvement of processes, focusing on the elimination of errors. In the unitary operations laboratory at the engineering faculty there is a trays dryer for educational purposes, but unfortunately does not provide reliable data to be able to carry out quality research because there are no adequate temperature conditions that each product requires to be dry. In the present investigation the appropriate elements were chosen to automate this type of dryer, considering the necessary control for temperature and drying time, but without altering the initial design of the equipment; therefore, the technical parameters with which the equipment was built to select each of the necessary elements such as a pt100 thermocouple, an expansion module for a LOGO!, analog signals interpretation a 220v-12v-24v- power supply for the operation of the console, contactors associated with the resistors and an associated relay for the fan. As a result, a drying process under control that complies with the established recommendations is obtained, thus providing reliable data for each product.